Spatial cognition XII : 12th international conference, Spatial Cognition 2020, Riga, Latvia, August 26-28, 2020 proceedings /: 12th international conference, Spatial Cognition 2020, Riga, Latvia, August 26-28, 2020 proceedings. (2020) - Unknown
No abstract available